2010
DOI: 10.1002/prca.200900050
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic examination of Leishmania chagasi plasma membrane proteins: Contrast between avirulent and virulent (metacyclic) parasite forms

Abstract: Leishmaniasis annually leads to two million new cases with 59 thousand deaths worldwide. Promastigotes of the causative Leishmania spp. develop from procyclic (log) to the highly virulent metacyclic stage within the sand fly vector. We hypothesized that proteins important for promastigote virulence might be uniquely represented in the plasma membrane of metacyclic, but not log, promastigotes. Purified metacyclic promastigotes from stationary phase cultures of Leishmania chagasi were applied to prepare membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 43 publications
4
22
1
9
Order By: Relevance
“…in the genomes of A. deanei and S. culicis , respectively. Proteins belonging to this group of zinc metalloproteases, also known as major surface protease (MSP) or leishmanolysin, have been characterized in various species of Leishmania and Trypanosoma [111]. Extensive studies on the role of this family in Leishmania indicate that they are involved in several aspects of host-parasite interaction including resistance to complement-mediated lysis, cell attachment, entry, and survival in macrophages [112].…”
Section: Resultsmentioning
confidence: 99%
“…in the genomes of A. deanei and S. culicis , respectively. Proteins belonging to this group of zinc metalloproteases, also known as major surface protease (MSP) or leishmanolysin, have been characterized in various species of Leishmania and Trypanosoma [111]. Extensive studies on the role of this family in Leishmania indicate that they are involved in several aspects of host-parasite interaction including resistance to complement-mediated lysis, cell attachment, entry, and survival in macrophages [112].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the temperature and speed of freezing seem to be key factors that influence its effectiveness. In a study where cells were suspended in hypotonic buffer and processed by five cycles of freezing in −80°C and thawing in a RT water bath, microscopy revealed that about 10% of the cells were not disrupted . In another study, a dry ice/ethanol bath was used to freeze red blood cells in hypotonic lysis buffer .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Leishmania has been mainly studied by LC‐MS [], including the mode of action of antimonial drugs []. This will afford the comparison with Leishmania fingerprinting by CE‐MS, which to the best of our knowledge has not been previously carried out.…”
Section: Introductionmentioning
confidence: 99%